Management of Patients with Guillain-Barré Syndrome in the Intensive Care Unit - Sani , Fahmi; Suwarman, Suwarman (CoinReads Media Prima, 2025)
Introduction: Guillain-Barré Syndrome (GBS) is an autoimmune disorder that affects the peripheral nervous system, commonly presenting with tetraplegia with or without sensory disturbances. This condition manifests as progressive muscle weakness and areflexia, leading to respiratory muscle weakness in severe cases, which often requires mechanical ventilation. ICU complications such as nosocomial infections, hospital-acquired pneumonia (HAP), ventilator-associated pneumonia (VAP), and sepsis are commonly encountered in prolonged hospitalizations. Plasmapheresis therapy is a primary treatment option for GBS, alongside intravenous immunoglobulin (IVIG). Case Report: We report the case of a 42-year-old male patient diagnosed with GBS, who developed respiratory failure and was treated with plasmapheresis. The patient showed significant clinical improvement following three cycles of plasmapheresis, leading to earlier recovery. The patient was successfully weaned off mechanical ventilation after four days. Conclusion: GBS is an autoimmune disorder following infection, leading to nerve cell destruction. Severe muscle weakness can result in respiratory failure, necessitating mechanical ventilation therapy.